L-Arginine Improves Cognitive Impairment in Hypertensive Frail Older Adults - Mone, Pasquale; Pansini, Antonella; Jankauskas, Stanislovas S.; Varzideh, Fahimeh; Kansakar, Urna; Lombardi, Angela; Trimarco, Valentina; Frullone, Salvatore; Santulli, Gaetano (Frontiers in Cardiovascular Medicine, 2022)
Cognitive impairment is a prevailing event in hypertensive patients and in frail older adults. Endothelial dysfunction has been shown to underlie both hypertension and cognitive dysfunction. Our hypothesis is that L-Arginine, which is known to ameliorate endothelial dysfunction, could counteract cognitive impairment in a high-risk population of hypertensive frail older adults. We designed a clinical trial to verify the effects of 4-weeks oral supplementation of L-Arginine on global cognitive function of hypertensive frail older patients. The study was successfully completed by 35 frail hypertensive elderly patients assigned to L-Arginine and 37 assigned to placebo. At follow-up, we found a significant difference in the Montreal Cognitive Assessment (MoCA) test score between the L-Arginine treated group and placebo (p: 0.0178). Moreover, we demonstrated that L-Arginine significantly attenuates Angiotensin II-induced mitochondrial oxidative stress in human endothelial cells. In conclusion, our findings indicate for the first time that oral L-Arginine supplementation significantly improves cognitive impairment in frail hypertensive older adults. Clinical Trial Registration www.ClinicalTrials.gov, identifier: NCT04962841.